Sciatic Nerve Traction Injuries in THR after Old Trauma of Neck of Femur Fracture more Than 3 Months - Usman Zafar Dar, Mohammad Nauman Shahid, Ali Muqaddas, Muhammad Ahmed, Sameer Ahmed, Naeem Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The purpose of this study is to measure the sciatic Nerve injuries in Total Hip Replacement after the old trauma of femur fracture more than 3 months. Materials and Methods. The design of this study was retrospective study design and this study was conducted at DHQ Teaching Hospital Gujranwala. Data was collected of Total 50 patients who underwent Total Hip Replacement following trauma of NECK of femur fracture. All Patients underwent through Total Hip Replacement surgery. Sciatic nerve traction injuries were noted. SPSS – 16 was used for statistical analysis of the data and for the calculation of the mean and SD. Mann-Whitney U test and Student’s t- test were also used for the analysis of the mean and SD in consideration with the p-value of (< 0.05). Results: Out of 50 patients, 5 patient developed Sciatic nerve injuries and 1 developed Femoral nerve injury. Out of these 5 Patients, cause of sciatic nerve injury in 3 patients was formation of hematoma and the cause of 2 sciatic nerve injuries and femoral nerve injury was trapping of the nerve due to scarring. However, the outcome of 4 out of 6 (66.66%) patients was Good, 1 (16.66%) had satisfactory result while the one patient (16.66%) with sciatic nerve injury developed total paralysis with poorer prognosis. Practical Implication: Sciatic nerve traction injuries can occur as a complication of total hip replacement (THR) surgery, especially after old trauma such as neck of femur fracture that occurred more than 3 months prior to the surgery. Such injuries can result in significant pain, weakness, and other functional impairments that can affect the patient’s quality of life. Therefore, it is important for surgeons to carefully evaluate the patient’s medical history and perform appropriate diagnostic tests to identify the risk of nerve injury before THR surgery. Furthermore, during surgery, surgeons should use techniques to minimize the risk of nerve injury, such as careful placement of implants and avoiding excessive traction on the sciatic nerve. Early detection and prompt management of sciatic nerve traction injuries can help to optimize patient outcomes and prevent long-term disability Conclusion: Sciatic Nerve injuries are common in THR after trauma to the neck of femur. So, these must be ruled out and proper management should be done. Keywords: Total Hip Replacement, Femur Neck Fracture, Sciatic Nerve Injury, Trauma.